The Impact of Data Breaches in Smart Manufacturing: An Analysis of Cost and Mitigation Strategies - Nagaraj, Ganesh (Digital Repository of Theses, 2024)
In Industry 4.0, smart manufacturing systems, in spite of their productivity and efficiency, they encounter major cyber security risks more so the data breaches. My research thus looks at these threats as well as the various costs that result out of them in relation to smart manufacturing. It also assesses existing reduction strategies while outlining a holistic safety framework: SMART SAFE (Systematic Monitoring, Analysis, and Response Technologies - Security Assessment, Fraud Prevention, and Evasion Detection). To measure the direct and long-term impacts of data breaches, evaluate current mitigation mechanisms and test the effectiveness of SMART-SAFE. This study is grounded on a mixed- methods research approach that combines literature review with case studies. Evidences demonstrate that there are complicated expenses emanating from data breaches whereas current approaches do not offer airtight solutions for protecting systems from sophisticated cyber-attacks. Moreover, it has been observed that combining systematic monitoring with advanced analysis technologies together with response technologies like security assessment, threat forecasting techniques and evasion techniques are some of the most effective and efficient ways possible under this system.